"Whether God exists" - Ostrowick, John M (Department of Philosophy, 2017)
This thesis presents inductive and probabilistic arguments for and against theism. The thesis claims that the only compelling evidentialist argument for theism is the cosmological argument from Richard Swinburne. Swinburne's argument is examined from a Bayesian perspective, and it is found that we can't fix the prior probabilities that Swinburne needs, not even by his appeal to simplicity. We then explain that this undermines P-inductive arguments, in particular, the cosmological argument. Then we consider whether theism offers a good explanation for the universe, or has a high likelihood, even if God is not simple. We find that there is no good reason to say that theism explains the universe better than competing theories. We therefore conclude that there is no C-inductive argument from cosmology to theism either. We then debate the physicalist explanations of the universe, which turn out to not help the atheist. We might feel that this leaves us in an argumentative stalemate, but in the final chapter, we turn to the problem of evil. We discuss the possible existence of gratuitous evils (evils which achieve no good ends). We then argue that the most plausible response to gratuitous evil is Skeptical Theism, that is, that we are unable to know God's intentions. But that stance undermines the cosmological argument which requires that we know God's intentions. We then conclude that, given that the cosmological argument is the most compelling evidential argument for theism, and that it fails, that the theist should abandon natural theology. Therefore, holding the fideist/voluntarist position, or that God is in fact indifferent to us, are found to be stronger stances.